As práticas de acolhimento como estratégia de integração e permanência no ensino médio integrado: uma investigação à luz da teoria fundamentada nos dados - Viana, Herleide Batista (2025)
The present study, within the research line “Educational Practices in Professional and Technological Education”, follows the guidelines of the macro-project “Educational Practices in the Integrated Curriculum”, which is grounded on the pillars of work, science, technology, and culture in the context of Professional and Technological Education (PTE), in accordance with the directives of the Professional Master’s Program in Professional and Technological Education (ProfEPT). In this context, the aim was to develop an explanatory theory regarding the welcoming practices directed at students entering Integrated Secondary Education with Professional and Technological Education, in such a way that it could contribute to their integration and retention at Campus Manaus Centro – IFAM. The research was based on a qualitative approach due to the nature of the research problem, enabling the capture of intricate details of the phenomenon, such as feelings, thought processes, and emotions. To collect the data, we conducted semi-structured interviews with 15 (fifteen) first-year students in the 2024 academic year, including class representatives and vice-representatives from the integrated technical high school courses. Data analysis, carried out through Grounded Theory, in the Constructivist perspective of Kathy Charmaz (2009), encompassed initial coding, focused coding, and theoretical coding. The investigation had the following specific objectives: a) To understand the welcoming practices implemented by Campus Manaus Centro, from the students’ perspective, aimed at the process of integration and the development of institutional identity, fostering a sense of belonging as a strategy for integration and retention; b) To identify the welcoming practices that contribute to the integration and retention of incoming students in Integrated Secondary Education with Professional and Technological Education at Campus Manaus Centro; c) To construct a Guide for New Students in Integrated Secondary Education, with guidelines for the process of integration and retention in this educational modality. The main outcome of this research was the understanding of the newcomers’ perceptions regarding the process of integration and retention in Integrated Secondary Education, expressed through the Substantive Theory: “Welcoming in Integrated Secondary Education is a continuous and multidimensional process that directly influences students’ integration, sense of belonging, and retention, depending on the interaction between institutional strategies and networks of academic and emotional support.”